2008
DOI: 10.1016/j.bbrc.2008.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Desulfitobacterium hafniense PylSc, a pyrrolysyl-tRNA synthetase

Abstract: Pyrrolysine, the 22nd genetically-encoded amino acid, is charged onto its specific tRNA by PylS, a pyrrolysyl-tRNA synthetase. While PylS is found as a single protein in certain archaeal methanogens, in the Gram-positive bacterium Desulfitobacterium hafniense, PylS is divided into two separate proteins, PylSn and PylSc, corresponding to the N-terminal and C-terminal domains of the single PylS protein found in methanogens. Previous crystallographic studies have provided the structure of a truncated C-terminal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
(55 reference statements)
1
29
0
Order By: Relevance
“…5) As compared to archaeal PylRS, the amino acid residues associated with the substrate side-chain carbonyl group are conserved in DhPylRS, suggesting that DhPylRS also requires a carbonyl group at the side-chain amino group for substrate recognition. 4,11) Consistently with this, it has been demonstrated that DhPylRS also recognizes Lys(Cyc) as a substrate.…”
Section: )supporting
confidence: 62%
See 2 more Smart Citations
“…5) As compared to archaeal PylRS, the amino acid residues associated with the substrate side-chain carbonyl group are conserved in DhPylRS, suggesting that DhPylRS also requires a carbonyl group at the side-chain amino group for substrate recognition. 4,11) Consistently with this, it has been demonstrated that DhPylRS also recognizes Lys(Cyc) as a substrate.…”
Section: )supporting
confidence: 62%
“…11,12) However, unlike M. barkeri PylRS, the substrate specificity of DhPylRS has not yet been well investigated, and only a few studies have been reported. 12) Recent protein engineering efforts make it possible to add non-canonical amino acids to the genetic code.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of Genes and Purification of Products-The D. hafniense PylSc and M. barkeri PylS proteins were purified following recombinant expression of their genes as described previously (14,30). The D. hafniense pylSn gene was amplified by PCR from genomic DNA using Ex Taq (Takara Mirus Bio, Madison, WI) and primers PylSnF and PylSnR (the sequence of these and other primers are listed in supplemental Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…The deletion was necessary to eliminate the highly basic yet hydrophobic N-terminal portion of the protein, whose presence interfered with protein stability and crystallization (29). The structure of D. hafniense PylSc is similar to that of M. mazei ⌬185PylS, although with an apparently tighter binding pocket for pyrrolysine (13,30). PylSc binds tRNA Pyl primarily through interactions with residues of the acceptor and D stem with no direct contact to residues of the T arm, anticodon arm, or variable loop (13).…”
mentioning
confidence: 99%